2019
DOI: 10.3329/jbcps.v37i3.41733
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Malocclusion in Patients Attended in Orthodontic Department of a Tertiary Level Hospital

Abstract: The aim of this study was to determine the pattern of individual traits of malocclusion, including sagittal molar relationship, overbite, overjet, crowding, spacing, cross bite, missing tooth, impacted tooth and extra tooth of upper and lower jaws in patients attended in Orthodontic Department of a Tertiary Level Hospital. This cross-sectional study included orthodontic patients who visited the department of Orthodontics and Dentofacial Orthopedics in Sapporo Dental College and Hospital from January 2013 to Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
(5 reference statements)
4
4
0
Order By: Relevance
“…In the present study the most frequently observed occlusal attributes in all type of malocclusion was deep bite (206, 73.57%) followed by increased over jet, crowding, and spacing. This result is similar to the study done by Pandey et al 8 but in a study done by Sufia et al 15 crowding was seen most prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study the most frequently observed occlusal attributes in all type of malocclusion was deep bite (206, 73.57%) followed by increased over jet, crowding, and spacing. This result is similar to the study done by Pandey et al 8 but in a study done by Sufia et al 15 crowding was seen most prevalent.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the malocclusion pattern present study result found that according to Angle's classification Class I malocclusion was the most prevalent type of malocclusion with 55.5 % , 38.3 % Class II and 6.3 % Class III among the examined Bangladeshi orthodontic patients, which was consistent with other studies reported by Rita SN et al [10] , Rahman MM et al [13] , and inconsistent with the studies [14,15] in India and [16] in Pakistan.…”
Section: Discussionsupporting
confidence: 90%
“…Present study assessed the malocclusion pattern among the Bangladeshi patients seeking for orthodontic treatment to provide quantitative information regarding the pattern of dentofacial characteristics. According to the study result majority (68.7 %) orthodontic patients were female, which supports the study results [10][11][12] , the reason behind this may be female are more concern about aesthetic issues than male.…”
Section: Discussionsupporting
confidence: 84%
“…22 Others contemporary literature existing in Bangladesh context publishes similar data from hospital setup. 10,11,13 However, in Asian context, literature has reported Class II malocclusion also as more frequent than Class I and III malocclusion in Asians. 23 By knowing the occlusal problems, their prevalence and need for appropriate treatment, helps us to plan the treatment necessary thus increasing the scope of orthodontics in future.…”
Section: Discussionmentioning
confidence: 99%
“…24%) were female and rest are male (fig.2) that correlates consisted with study of Rita et. al 10 ,. Rubby et.…”
mentioning
confidence: 99%